Performance Enhancement for Optical OFDM System using Modified PAPR Reduction Algorithm - VandanaTripathi, Prabhat Patel, Prashant KumarJain (Mathematical Statistician and Engineering Applications, 2022)
Wireless technology is one of the new developments in the field of communication. This provides efficient data transfer and increasing 4 G and 5 G networking framework. The definition of a multi-carrier modulation is specified by an OFDM system. The OFDM is affected by the disadvantage of high PAPR i.e. peak to average power ratio. In this paper several strategies have been discussed like SLM, PTS, Tone Reservation, Clipping and Filtering, etc. to reduce the PAPR effect in OFDM system. The study of various PAPR reduction strategies involve specific parameters such as distortion rate, data size, power increase etc.We have proposed an optimal and sub-optimal scheme for SSR ICI cancellation scheme to improve the CIR performance. The scheme is based on SSR ICI self cancellation scheme, in which a data is modulated at two symmetrically placed subcarriers i.e. and N-1- and utilizes a data allocation of (1,-?) to improve CIR performance. To further reduce the effect of ICI, received modulated data signal at and N-1- subcarriers are combined with weights 1 and -. The ? and ? are the optimal values resulting in maximum CIR. The optimum values of ? and ? are the function of normalized frequency offset i.e. for every normalized frequency offset; there exist a unique value of ? and ?. This process requires continuous CFO estimation. To overcome this problem, we have proposed a suboptimal approach to find suboptimal values. The obtained sub-optimal values are independent of normalized frequency offset. Thus, the proposed scheme does not require any CFO estimation or feedback circuitry and hence eliminates the requirement of complex hardware circuitry.